Posted by **merx** on Friday, November 12, 2010 at 2:30am.

if y1=x^(2)+3x-1 and y2= x-5

find:

a. y1+y2

b. y1-y2

c. y1*y2

- function -
**Henry**, Friday, November 12, 2010 at 7:31pm
a. Y1 + Y2 =( X^2 + 3X - 1) + (X - 5),

X^2 + 3X - 1 + X - 5,

X^2 +4X - 6.

b. Y1 - Y2 = (X^2 + 3X - 1) -(X - 5),

X^2 + 3X - 1 -X + 5,

X^2 + 2X + 4,

c. Y1 * Y2 = (X^2 + 2X + 4) (X - 5),

X^3 + 3X^2 - X - 5X^2 - 15X + 5,

X^3 - 2X^2 - 16X + 5

## Answer This Question

## Related Questions

- Calulus - Consider the function y = 2x^3-3x^2+9x+5. 1. Find where the function ...
- calc - Consider the function below. (Round the answers to two decimal places. f(...
- CAL - Hi, im lost in theses three problems. Please help. Thank you so much!!! 1...
- Math22 - 1. Write the composite function in the form f(g(x)). [Identify the ...
- calculus - 8. Find the derivative of the function f(x) = cos^2(x) + tan^2(x) 9...
- MATH - We now have d dx [x5 + y8] = 5x4 + 8y7y' = d dx [9] = 0. Rearranging this...
- Maths - Question – 1: The gradient of the graph of f(x) at any point is,ax^2-12x...
- Maths - Demand function P=50-Q Average Cost 5Q + 40 +10/Q Calculate the firm's ...
- math - We fire a missile from ground level at 1750 ft/sec. at launch angle of 10...
- pre-cal: graphs of functions- fill in the blank - To find the domain of a ...

More Related Questions